Synthesis of S‐Trifluoromethyl S‐Arylsulfoximine Thioglycosides through Pd‐Catalyzed Migita Cross‐Coupling. Issue 31 (16th July 2020) - Bennai, Nedjwa; Ibrahim, Nada; Marrot, Jérôme; Belkadi, Mohamed; Alami, Mouad; Magnier, Emmanuel; Anselmi, Elsa; Messaoudi, Samir
Abstract : A general protocol for the synthesis of S‐trifluoromethyl S‐arylsulfoximine thioglycosides has been reported. This protocol is based on a Pd‐catalyzed Migita cross‐coupling between o ‐iodo S‐trifluoromethyl S‐arylsulfoximines and a broad range of 1‐thiosugars. This method gives access to a series of functionalized S‐trifluoromethyl S‐arylsulfoximine thioglycosides in moderate to good yields. Moreover, both diastereoisomers were easily separated by simple crystallization or by HPLC and full characterizations are provided for each pure trifluoromethylsulfoximine. Abstract : A Pd‐catalyzed method for the synthesis of S‐trifluoromethyl S‐arylsulfoximine thioglycosides has been reported. Moreover, both diastereoisomers were easily separated by simple crystallization or by HPLC and full characterizations are provided for each pure trifluoromethylsulfoximine.